Distraction osteogenesis in the craniomaxillofacial region. Part II: peri operative issues, surgical procedure, complications and reliability - Mahdah, Saridah; Chi Adam, Khairul Bariah; Azmi, MN; Saleh, I; Nabil, S; Hariri, Firdaus (Malaysian Association Of Oral Maxillofacial Surgeons, 2015)
Distraction osteogenesis(DO) has been revolutionized in the past 20 years. Ever since the technique was introduced by Ilizarov, the application of this technique been extended into various region in human body including in craniomaxillofacial region. Extensive research in various aspects of this technique has been done to provide scientific evidence and better understanding thus optimizing the surgical outcome to patients. The superiority of DO in overcoming limitations in conventional surgery resulted in greater application in treating deformity over the craniomaxillofacial region. This second part of DO application in craniomaxillofacial region article emphasizes on theclinical aspects of DO focusing on the peri-operative issues, important surgical aspects, related complications and reliability of this technique. Understanding of the clinical and technical components of DO will ensure favourable and predictable outcome when DO become the treatment of choice.